Studies in the Synthesis of 1,2 and 9-substituted Phenothiazin-3 and 7-ols and their Derivatives - Khatri nee Taneja, Vineeta; Gupta nee Garg, Urmila; Sareen nee Grover, Vineeta; Sharma, Kanti (Asian Journal of Chemistry, 2010)
1,2 and 9-substituted phenothiazin-3 and 7-ols have been synthesized by the condensation of chloro hydroquinone with various zinc salts of 2-arnino-3-chlorolmethyl benzenethiols and 2-arnino- 4-bromobenzenethiol in oxygen stream in ethanol via Mine's condensation: Their methoxy, isopropoxy, benzyloxy, acetate (esters) and benzoate (esters) have also been synthesized. The compounds synthesized are characterized by their spectral (IR, mass) and analytical data. Their Rf and relative Rf values by TLC have also been discussed.